1983
DOI: 10.1111/j.1365-246x.1983.tb03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Test of tectonic models by great circle Rayleigh waves

Abstract: A large set of published great circle Rayleigh wave phase velocities in the period range 125-350s is used to compare three recent tectonic models (Okal, UvEque, Jordan). Prior to any regionalization, the symmetry property of the great circle integrals is used to obtain a lower limit of the signal/noise ratio in the data. It turns out that the signal is responsible for at least 30 per cent of the data variance in the period range 175-300 s.A standard regression method is applied for computing the 'pure path' ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…[19], had claimed that the inner core had a different rotation rate than the mantle by about 3 • per year. However by comparing normal mode measurements over the last twenty years, Laske and Masters [13] found that this rotation difference is less than 0.13 • ± 0.11 • yr −1 , which is consistent with other seismic data [20] and with the idea that the inner core is gravitationally locked to the mantle. This issue is not completely solved yet.…”
Section: Rotational Splitting: the Great Sumatra-andaman Earthquakesupporting
confidence: 79%
“…[19], had claimed that the inner core had a different rotation rate than the mantle by about 3 • per year. However by comparing normal mode measurements over the last twenty years, Laske and Masters [13] found that this rotation difference is less than 0.13 • ± 0.11 • yr −1 , which is consistent with other seismic data [20] and with the idea that the inner core is gravitationally locked to the mantle. This issue is not completely solved yet.…”
Section: Rotational Splitting: the Great Sumatra-andaman Earthquakesupporting
confidence: 79%
“…Two continental types are defined: mountainous regions (M) and shields (S). This regionalization is successful in reducing the variance of great circle observations (Souriau and Souriau, 1983). The variance reduction for great circle phase velocity measurements amounts to about 80% for Rayleigh waves and 60% for Love waves for periods from 150 to 300 s (NA 1 ).…”
Section: Regionalized Phase Velocitiesmentioning
confidence: 98%
“…Depending on the appropriateness of the a priori choice, the way that great circle observations are actually explained varies. Souriau and Souriau (1983) have tested the variance reduction achieved by several proposed regionalizations and concluded that the regionalization of Okal (1977) was the best. It includes four oceanic regions corresponding to different age slices of the seafloor, a region for trenches and marginal seas, a shield region, and a mountainous region.…”
Section: Introductionmentioning
confidence: 99%
“…oid ocean contained only Mitchell and Yu's data when the models were determined, However, the Rayleigh phase velocity data of Souriau and Souriau [1983] were added after the model was derived. These data, which fit the model already calulated to within two standard deviations, are based on a pure path analysis ut*ing the combined velocity data of Kanamori [1970], Dziewonski [1970], Wu [1972], Dziewonski and Gilbert [1972], Okal [1977], Nakanishi [1979], and Leveque [1983] were compared with the models, and generally agree with these except in the 50-100 M.Y, old province.…”
Section: Datamentioning
confidence: 99%